Design, Formulation, and Evaluation of Sustained Release Tablets for Antihyperlipidemic Agent - Gopaiah, Mr. K. Venkata (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Objective: The main objective of the present research investigation is to formulate the sustained release (SR) formulation of rosuvastatin. Rosuvastatin, an antihyperlipidemic agent, belongs to Biopharmaceutical Classification System class-II agent. Materials and Methods: The SR tablets of rosuvastatin were prepared by employing different concentrations of hydroxy methyl propyl cellulose (HPMCK4M) and sodium carboxymethyl cellulose (SCMC) in different combinations by direct compression using 32 factorial designs. The concentration of polymers, HPMCK4M, and SCMC required to achieve the desired drug release was selected as independent variables, X1 and X2, respectively, whereas time required for 10% of drug dissolution (t10%), 50% (t50%), 75% (t75%), and 90% (t90%) was selected as dependent variables. Results and Discussion: A total of nine formulations were designed and are evaluated for hardness, friability, thickness, % drug content, and in vitro drug release. From the results, it was concluded that all the formulations were found to be within the pharmacopeial limits and the in vitro dissolution profiles of all formulations were fitted into different kinetic models; the statistical parameters such as intercept, slope, and regression coefficient were calculated. Polynomial equations were developed for dependent variables. The validity of developed polynomial equations was verified by designing 2 check point formulations (C1 and C2). According to SUPAC guidelines, the formulation (F4) containing 30 mg of HPMCK4M and 40 mg of SCMC is the most similar formulation (similarity factor f2= 89.561, dissimilarity factor f1 = 1.543, and no significant difference, t = 0.0056) to marketed product (CRESTOR). Conclusion: The selected formulation (F4) follows zero-order and Higuchi kinetics, and the mechanism of drug release was found to be non-Fickian Diffusion (n = 0.963).